2003
DOI: 10.1007/s10227-002-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid Follicular Hamartoma with Trichoblastomatous Proliferations

Abstract: While trichoblastomatous proliferations could occur in a BFH, to our knowledge this finding has not been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The linear and unilateral type of BFH may be present at birth , as in our first patient; appear during childhood , as in our second patient; or develop during puberty . The most important clinical feature in this type of BFH is the unilateral and linear distribution of the lesions that in almost all patients might be associated with the lines of Blaschko .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The linear and unilateral type of BFH may be present at birth , as in our first patient; appear during childhood , as in our second patient; or develop during puberty . The most important clinical feature in this type of BFH is the unilateral and linear distribution of the lesions that in almost all patients might be associated with the lines of Blaschko .…”
Section: Discussionmentioning
confidence: 55%
“…In three patients, BCCs developed within the linear and unilateral type of BFH . A patient with linear and unilateral BFH with an unusual, extensive proliferation of trichoblastoma has also been reported . Moreover, it may occur in association with Happle–Tinschert syndrome, characterized by segmentally arranged BFHs associated with ipsilateral osseous, dental, and cerebral abnormalities .…”
Section: Discussionmentioning
confidence: 95%
“…Kaiser et al 10 reported a linear, solitary form of BFH that featured trichoblastomatous proliferations. Clinically, misdiagnosis of these conditions are BCC, sebaceous hyperplasia, seborrheic keratosis, and nevi of melanocyte [2][3][4]11 .…”
Section: Discussionmentioning
confidence: 99%
“…Linear BFH generally occurs in isolation although association with various disorders [Table 1] and development of BCC in the lesions have been described as well. [23] Clinical differential diagnoses of linear BFH include unilateral nevoid BCC syndrome, linear forms of epidermal and eccrine nevi, and Blaschkoid variants of trichoepithelioma, eccrine spiradenoma, eccrine poroma, and syringoma. [2]…”
mentioning
confidence: 99%